Reclaiming structural steels from the end of service life composite structures for reuse – An assessment of the viability of different methods. (May 2022) - Chen, Han-Mei; Wang, Yong; Zhou, Kan; Lam, Dennis; Guo, Wei; Li, Lin; Ajayebi, Atta; Hopkinson, Peter
Abstract: The ability to separate structural steel sections from concrete slabs in composite beams without damage forms a key technical challenge for reclaim and direct re-use of composite structures as opposed to recycling. This paper addresses this technical challenge. It presents the results of a feasibility study using a variety of potential techniques, including laser cutting, band-saw cutting, wire-saw and wall-saw cutting, and diamond core drilling, to cut welded shear connectors in conventional steel-concrete composite beams with the steel sheeting perpendicular to the steel section. The most feasible reclaiming method was found to be wire-saw and wall-saw cutting. After reclaiming steel sections, steel tensile coupon tests were carried out on the recovered steel sections and their mechanical properties were compared to those of the original steel used in the composite beams. The coupon test results showed identical behaviour of the original and reclaimed steels. The energy use of the different methods of reclaiming was also recorded to calculate carbon emission and was found to be several orders of magnitude lower than manufacturing virgin steel or recycling steel. Highlights: It is technically feasible to reclaim steel from steel-concrete composite beams. The most technically feasible steel reclaiming method was wire-saw and wall-saw cutting. The mechanical behaviours of the original and reclaimed steels were identical. The energy use in reclaiming methods was several orders of magnitude lower than recycling.